The Subchalcogenides Ir2In8Q (Q = S, Se, Te): Dirac Semimetal Candidates with Re-entrant Structural Modulation - Khoury, Jason F; Rettie, Alexander J. E; Robredo, Iñigo; Krogstad, Matthew J; Malliakas, Christos D; Bergara, Aitor; Vergniory, Maia G; Osborn, Raymond; Rosenkranz, Stephan; Chung, Duck Young; Kanatzidis, Mercouri G (Journal of the American Chemical Society, 2020)
Subchalcogenides are uncommon compounds where the metal atoms are in unusually low formal oxidation states. They bridge the gap between intermetallics and semiconductors and can have unexpected structures and properties because of the exotic nature of their chemical bonding as they contain both metal–metal and metal–main group (e.g., halide, chalcogenide) interactions. Finding new members of this class of materials presents synthetic challenges as attempts to make them often result in phase separation into binary compounds. We overcome this difficulty by utilizing indium as a metal flux to synthesize large (millimeter scale) single crystals of novel subchalcogenide materials. Herein, we report two new compounds Ir2In8Q (Q = Se, Te) and compare their structural and electrical properties to the previously reported Ir2In8S analogue. Ir2In8Se and Ir2In8Te crystallize in the P42/mnm space group and are isostructural to Ir2In8S, but also have commensurately modulated (with q vectors q = 1/6a* + 1/6b* and q = 1/10a* + 1/10b* for Ir2In8Se and Ir2In8Te, respectively) low-temperature phase transitions, where the chalcogenide anions in the channels experience a distortion in the form of In–Q bond alternation along the ab plane. Both compounds display re-entrant structural behavior, where the supercells appear on cooling but revert to the original subcell below 100 K, suggesting competing structural and electronic interactions dictate the overall structure. Notably, these materials are topological semimetal candidates with symmetry-protected Dirac crossings near the Fermi level and exhibit high electron mobilities (∼1500 cm2 V–1 s–1 at 1.8 K) and moderate carrier concentrations (∼1020 cm–3) from charge transport measurements. This work highlights metal flux as a synthetic route to high quality single crystals of novel intermetallic subchalcogenides with Dirac semimetal behavior.